Analisis Hukum Terhadap Penipuan Dengan Modus Donasi Online Berdasarkan Undang-Undang Nomor 19 Tahun 2016 - Ghozali, Ahmad; Faridah, Hana (Peneliti.net, 2023)
The rise of fraud in the digital era has forced the government to prepare regulations in line with the development of fraudulent technology in accordance with Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 Concerning Electronic Information and Transactions, article 28 paragraph 1 states,